‘Research on Clinical Significance of Blood groups on Bleeding time and Clotting Time and its Association with Diseases; An Advanced Study’ - M. Bagavad Geetha; Jiby Jolly Benjamin (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
Background: Blood group plays a unique role in revealing the identity of an individual. Studies have shown that certain diseases and personality features vary among ABO blood groups. In addition, variations in terms of bleeding tendencies among these blood groups have also been unleashed. Hence a study was done to the find association of bleeding time (BT) and clotting time (CT) with ABO blood group. Methods and Materials: This study had a cross-sectional study design and was done among 250 young adults aged between 18 and 24 years. Slide agglutination method was used to assess ABO blood group; while Dukes and capillary tube method were used to determine BT and CT respectively. Statistical Analysis: Chi-square analysis was done to analyze the association of BT and CT with blood group. Statistical significance was considered when p value was less than 0.05. Aim & Objectives: To determine the predominant ABO blood group among the young adult population and to find the association between ABO blood group with bleeding time and clotting time and to assess the gender variation in bleeding time and clotting time among the young adult population. Conclusion: In this study, results have shown that blood group O was the predominant blood group among the study population and blood group O and B had prolonged BT and CT compared to other groups. Based on gender, females had higher CT compared to males.